Green Tea Extracts as Natural Antimicrobial Agents: A Comparative Analysis Against Periodontal Disease-Causing Bacteria - Khan, Mohammad Oliur Rahman; Ali, Mir Nowazesh; Khanam, Jahan Ara (Journal of Dentistry and Allied Science, 2025)
Green tea (Camellia sinensis) has been recognized for its health-promoting properties, notably its antimicrobial and antioxidant effects. This study compares the antimicrobial efficacy of green tea extracts obtained using different solvents (ethanol, methanol, acetone, and water) against periodontal pathogens such as Porphyromonas gingivalis and Streptococcus sanguinis. Bioactive compounds were analyzed using column chromatography extraction. The ethanolic extract showed the highest levels of key components like epigallocatechin gallate (EGCG) and caffeine and demonstrated significant antimicrobial activity with zones of inhibition up to 12.34 ± 1.04 mm for Porphyromonas gingivalis. These results suggest that green tea extracts, particularly ethanol-based extract, could be effective natural antimicrobial agents in combating periodontal disease. Journal of Dentistry and Allied Science, Vol. 8 No 2: 28-33